2022
DOI: 10.3389/fphar.2022.949754
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of myocardial ischemia/reperfusion injury in diabetes: A narrative review of the mechanisms and clinical applications of dexmedetomidine

Abstract: Mechanisms contributing to the pathogenesis of myocardial ischemia-reperfusion (I/R) injury are complex and multifactorial. Many strategies have been developed to ameliorate myocardial I/R injuries based on these mechanisms. However, the cardioprotective effects of these strategies appear to diminish in diabetic states. Diabetes weakens myocardial responses to therapies by disrupting intracellular signaling pathways which may be responsible for enhancing cellular resistance to damage. Intriguingly, it was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 109 publications
0
5
0
Order By: Relevance
“…Diabetes is an independent risk factor of ischemic heart disease. It aggravates the MIRI and the main cause of death of diabetes patients 10 . Finding drugs that can effectively reduce the MIRI of diabetes is one of the focuses of the current research.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes is an independent risk factor of ischemic heart disease. It aggravates the MIRI and the main cause of death of diabetes patients 10 . Finding drugs that can effectively reduce the MIRI of diabetes is one of the focuses of the current research.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, taking scientific and effective treatment measures to prevent myocardial hypoxia-reoxygenation injury is instrumental in enhancing the prognosis of individuals afflicted with myocardial infarction. It has been found that after the occurrence of hypoxic-ischemic myocardial injury, the body initiates a series of sequence reactions, including apoptosis, inflammation, disturbance of energy metabolism, oxidative stress and so on [8,9] .…”
Section: Groupmentioning
confidence: 99%
“…Dexmedetomidine (DEX), a highly selective α-adrenergic receptor agonist, is widely used in clinical practice. DEX can be used in combination with other narcotic drugs to achieve better analgesia, sedation and adverse stress control during coronary artery bypass surgery [24]. Studies have shown that DEX could promote cardiomyocyte survival by activating PI3K/AKT, SIRT1/mTOR, MAPK/ERK and AMPK signaling pathways [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%